Identificación Molecular del ADN en Toxocara canis en caninos en Salcedo - Antamba Yépez, Marco Andrés (2021)
The present investigation was carried out in Cotopaxi Province, in Salcedo Canton´s neighborhoods, the objective of the study was to sequence the internal transcribed spacer region (ITS-2) of the ribosomal DNA (rDNA) of Toxocara canis. A total of 106 canine stool samples were collected from adults and puppies of both sexes. The population ranged in age from one month until nine years. The samples were taken from 3 to 5 grams of feces, the samples were taken in the laboratory of the Technical University of Cotopaxi in the Biology Laboratory, under the Sheather flotation technique. Sixteen canines were positive, showing the presence of Toxocara canis eggs (16.96 %) of prevalence according to the samples taken and analyzed by microscopy. To obtain the parasite, the population under study was orally dewormed, taking into account the nutritional and living conditions of the pet. The adult parasite was collected from 24 canines, indicating a 25.44 % presence of the nematode, based on the macroscopic morphology. In 8 canines from one month to six months old, deworming was performed without coprological examinations where parasites were expelled. The 20 samples isolated from canines were identified as Toxocara canis when compared using BLAST with sequences previously deposited in GenBank with 100% identity for T. canis. For the sequencing of the adult male parasite, it was proceeded to dissect following the process of preservation, the integrity of the biological sample, which guarantees the amplification, purification and sequencing of DNA, avoiding the dissection of reproductive organs and causing interference at the time of amplification of DNA fragments. The tests performed indicate high reliability in the diagnosis of molecular tools.